Bibliometrics The Relationship between OBSE (Organization-Based Self-Esteem) and Sustainability in HR - Judijanto, Loso; Malik, Abdul Hadi (Westscience Press, 2025)
This study offers a bibliometric examination of the correlation between Organization-Based Self-Esteem (OBSE) and sustainability in human resource management (HRM), utilizing data from the Scopus database spanning 2000 to 2025. The study utilizes VOSviewer and Bibliometrix software to delineate publishing trends, authorship networks, keyword co-occurrences, and topic evolution, thereby identifying intellectual tendencies and research deficiencies. Findings reveal that